Cloning and sequence analysis of genes for dehalogenation of 4-chlorobenzoate from Arthrobacter sp. strain SU. - Schmitz, A (1992)
Strains of Arthrobacter catalyze a hydrolytic dehalogenation of 4-chlorobenzoate (4-CBA) to p-hydroxybenzoate. The reaction requires ATP and coenzyme A (CoA), indicating activation of the substrate via a thioester, like that reported for Pseudomonas sp. strain CBS3 (J. D. Scholten, K.-H. Chang, P. C. Babbit, H. Charest, M. Sylvestre, and D. Dunaway-Mariano, Science 253:182-185, 1991). The dehalogenase genes of Arthrobacter sp. strain SU were cloned and expressed in Escherichia coli. Analyses of deletions indicate that dehalogenation depends on three open reading frames (ORFs) which are organized in an operon. There is extensive sequence homology to corresponding gene products in Pseudomonas sp. strain CBS3, suggesting that ORF1 and ORF2 encode a 4-CBA-CoA-ligase and a 4-CBA-CoA dehalogenase, respectively. ORF3 possibly represents a thioesterase, although no homology to the enzyme from Pseudomonas sp. strain CBS3 exists.